Kaplan’s Way with Skepticism - Williams, Michael (International journal for the study of skepticism, 2022)
Austin is not much in fashion these days. In Austin’s Way with Skepticism, Mark Kaplan swims against the current, arguing that Austin still has much to teach us about how to do epistemology. Methodologically, Austin’s insistence on fidelity to ordinary ways of talking about knowledge is a non-negotiable constraint on epistemological theorizing. Substantively, Austin has important things to say about knowledge. But while I am fully in accord with the spirit of Kaplan’s enterprise, I take Austin to occupy a more radical position: that getting the linguistic facts straight should lead us to call into question the very idea of a theory of knowledge, at least as ‘theory of knowledge’ has traditionally been understood.